Large-package and ensiled milo stover for maintaining pregnant cows - Kimple, K.; McKee, M.; Fink, G. (Kansas State University. Agricultural Experiment Station, 2011)
One hundred-two mature Simmental and Hereford cows in mid to late gestation were used to compare three maintenance rations during an 83-day trial: (1) milo stover silage, (2) large package milo stover (stacks and bales), and (3) forage sorghum silage. Each breed was represented by a pen of 17 cows in each of the forage groups. Cows fed forage sorghum silage gained significantly more than cows on other rations. Cows receiving milo stover silage lost heavily early because amounts were inadequate. They gained when stover silage was increased. Cows fed ad libitum on dry milo stover lost weight during the last 30 days of the trial.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Milo stover; Pregnant cows